Preliminary Quality Control of Magnetic Materials for applications in Restorative Medicine - Quantitative Analysis of Structural Homogeneity of RE-M-B /Polymer Composites - Klimecka-Tatar, Dorota; Pawłowska, Grażyna; Radomska, Klaudia (Manufacturing Technology Journal, 2020)
The properties of bonded magnetic materials (RE-M-B /polymer magnetic composites) depend not only on the magnetic properties of powder, but also on the parameters of the consolidation process and the type of binder. Increasing the binder content in RE-M-B /polymer composites could be very beneficial from the cor-rosion resistance point of view, which, unfortunately, is not conducive to the magnetic properties improve-ment. Therefore, a compromise between both trends is necessary to obtain a material with adequate corro-sion resistance with an acceptable decrease in magnetic properties. In the paper the results of research un-der Nd12Fe77Co5B / biotolerant-polymer composites with different binder content have been presented. The research has been carried out on Nd12Fe77Co5B / biotolerant-polymer composites with 20 and 10 wt. % of binder. Due to the possibility of using the magnetic material in restorative medicine, as a binder the bio-tolerable polymeric material has been used (acrylate). All results has been compared to previously deter-mined measurements for composite with a binder content about 3 % wt.. It has been found that the content of 10 % wt. bio-tolerable polymeric material in the magnetic composite is the most favorable (optimal) - the binder material is evenly distributed throughout the composite volume.
Keywords: quality control; bonded magnets; quantitative analysis; composite structure